Contributed to this edition (28.3): Contribuíram nesta edição (28.3) (Programa de Pós-graduação em Desenvolvimento, Agricultura e Sociedade da Universidade Federal Rural do Rio de Janeiro (CPDA/UFRRJ), 2020)
List of reviewers who contributed by evaluating articles during the period of preparation of this edition of the magazine Estudos Sociedade e Agricultura (v. 28, n. 3, October 2020 to January 2020).- Alexandra Martins Silva – Universidade Federal do Rio de Janeiro (UFRJ), Rio de Janeiro, Rio de Janeiro, Brasil- Ana Lúcia da Costa Silveira – Universidade Federal Rural do Rio de Janeiro (UFRRJ), Seropédica, Rio de Janeiro, Brasil- Ana Paula Schervinski Villwock – Universidade Federal de Sergipe (UFS), São Cristóvão, Sergipe, Brasil- Andréa Cristina Martins Pereira – Universidade Estadual de Montes Claros (Unimontes), Montes Claros, Minas Gerais, Brasil- Ângelo Magalhães Silva – Universidade Federal Rural do Semi-Árido (UFERSA), Mossoró, Rio Grande do Norte, Brasil- Antônio Fernando de Araújo Sá – Universidade Federal do Sergipe (UFS), São Cristóvão, Sergipe, Brasil- Arlete Fonseca de Andrade – Pontifícia Universidade Católica de São Paulo (PUC-SP), São Paulo, São Paulo, Brasil- Carmen Lucia Tavares Felgueiras – Universidade Federal Fluminense (UFF), Niterói, Rio de Janeiro, Brasil- Cicero Nilton Moreira da Silva – Universidade do Estado do Rio Grande do Norte (UERN), Pau dos Ferros, Rio Grande do Norte, Brasil- Cidonea Machado Deponti – Universidade de Santa Cruz do Sul (UNISC), Santa Cruz do Sul, Rio Grande do Sul, Brasil- Clóvis Dorignon – Empresa de Pesquisa Agropecuária e Extensão Rural de Santa Catarina (Embrapa/SC), Florianópolis, Santa Catarina, Brasil- Cristiano Desconsi – Universidade Federal de Santa Catarina (UFSC), Florianópolis, Santa Catarina, Brasil- Delma Pessanha Neves – Universidade Federal Fluminense (UFF), Niterói, Rio de Janeiro, Brasil- Everton Lazzaretti Picolotto – Universidade Federal de Santa Maria (UFSM), Santa Maria, Rio de Grande do Sul, Brasil- Fabiane Renata Borsato – Universidade Estadual Paulista Júlio de Mesquita Filho (Unesp), Araraquara, São Paulo, Brasil- Fabiano de Souza Gontijo – Universidade Federal do Pará (UFPA), Belém, Pará, Brasil- Fabiano Toni – Universidade de Brasília (UnB), Brasília, Distrito Federal, Brasil- Flávio Sacco dos Anjos – Universidade Federal de Pelotas (UFPel), Pelotas, Rio Grande do Sul, Brasil- Gilmar Rocha – Universidade Federal Fluminense (UFF), Rio das Ostras, Rio de Janeiro, Brasil- Guélmer Júnior Almeida Faria – Universidade Federal de Viçosa (UFV), Viçosa, Minas Gerais, Brasil- Haruf Salmen Espíndola – Universidade Vale do Rio Doce (Univale), Governador Valadares, Minas Gerais, Brasil- Izabel Missagia de Mattos – Universidade Federal Rural do Rio de Janeiro (UFRRJ), Seropédica, Rio de Janeiro, Brasil- Jairo Bezerra Silva – Universidade Estadual da Paraíba (UEPB), Campina Grande, Paraíba, Brasil- Jean Pierre Passos Medaets – Universidade de Brasília (UnB), Brasília, Distrito Federal, Brasil- João Paulo Macedo – Universidade Federal do Piauí (UFPI), Teresina, Piauí, Brasil- Julia Silvia Guivant – Universidade Federal de Santa Catarina (UFSC), Florianópolis, Santa Catarina, Brasil- Juliete Miranda Alves – Universidade Federal Rural da Amazônia (UFRA), Belém, Pará, Brasil- Júlio Cezar Bastoni da Silva – Universidade Federal do Ceará (UFC), Fortaleza, Ceará, Brasil- Larissa da Silva Ferreira Alves – Universidade do Estado do Rio Grande do Norte (UERN), Pau dos Ferros, Rio Grande do Norte, Brasil- Lorena Cândido Fleury – Universidade Federal do Rio Grande do Sul (UFRGS), Porto Alegre, Rio Grande do Sul, Brasil- Luiz Felipe Rocha Benites – Universidade Federal Rural do Rio de Janeiro (UFRRJ), Seropédica, Rio de Janeiro, Brasil- Luiz Gonzaga Marchezan – Universidade Estadual Paulista Júlio de Mesquita Filho (Unesp), Araraquara, São Paulo, Brasil- Maciel Cover – Universidade Federal do Tocantins (UFTO), Palmas, Tocantins, Brasil- Marcelino de Souza – Universidade Federal do Rio Grande do Sul (UFRGS), Porto Alegre, Rio Grande do Sul, Brasil- Márcio de Matos Caniello – Universidade Federal de Campina Grande (UFCG), Campina Grande, Paraíba, Brasil- Maria Celia de Moraes Leonel – Universidade Estadual Paulista (Unesp), Araraquara, São Paulo, Brasil- Maria Inês Gasparetto Higuchi – Universidade Federal do Amazonas (UFAM), Manaus, Amazonas, Brasil- Mariana Vieira Galuch – Universidade Federal do Amazonas (UFAM), Manaus, Amazonas, Brasil- Marilda Menezes – Universidade Federal do ABC (UFABC), Santo André, São Paulo, Brasil- Mário Lúcio de Avila – Universidade de Brasília (UnB), Brasília, Distrito Federal, Brasil- Mylene Nogueira Teixeira – Universidade Estadual do Norte Fluminense (UENF) – Campos dos Goytacazes, Rio de Janeiro, Brasil- Nelson Delgado – Universidade Federal Rural do Rio de Janeiro (UFRRJ), Rio de Janeiro, Rio de Janeiro, Brasil- Patricia Eveline dos Santos Roncato – Universidade Federal do Pampa (Unipampa), Santana do - Livramento, Rio Grande do Sul, Brasil- Ramonildes Alves Gomes – Universidade Federal de Campina Grande (UFCG), Campina Grande, Paraíba, Brasil- Renato Sérgio Maluf – Universidade Federal Rural do Rio de Janeiro (UFRRJ), Rio de Janeiro, Rio de Janeiro, Brasil- Roberto de Sousa Miranda – Universidade Federal do Agreste de Pernambuco (Ufape), Guaranhuns, Pernambuco, Brasil- Rosani Marisa Spanevello – Universidade Federal de Santa Maria (UFSM), Palmeira das Missões, Rio de Grande do Sul, Brasil- Rozane Marcia Triches – Universidade Federal da Fronteira Sul (UFFS), Chapecó, Santa Catarina, Brasil- Silvio Cezar Arend – Universidade de Santa Cruz do Sul (UNISC), Santa Cruz do Sul, Rio Grande do Sul, Brasil- Tania Mara Antonietti Lopes – Universidade de São Paulo (USP), São Paulo, São Paulo, Brasil- Thiago Araújo Santos – Universidade Federal de Mato Grosso do Sul (UFMS), Três Lagoas, Mato Grosso do Sul, Brasil- William Héctor Gómez Soto – Universidade Federal de Pelotas (UFPel), Pelotas, Rio Grande do Sul, Brasil- Wilma Martins de Mendonça – Universidade Federal da Paraíba (UFPB), João Pessoa, Paraíba, Brasil